POWER RELATIONS IN TWO CONTEMPORARY INDONESIAN NOVELS WITH POLITICAL THEMES - Adji, Susilawati Endah Peni (International Journal of Humanity Studies (IJHS), 2020)
Since Indonesia began its political reform in 1998, Indonesians have enjoyed increased freedom of expression, and as such it has been possible for long-censored themes such as politics to be freely discussed in contemporary Indonesian literature. This article examines two such novels, (1) Junaedi Setiono's Dasamuka (2017), which deals with Javanese politics during the Diponegoro War; and (2) Arafat Nur's Lolong Anjing di Bulan (Dogs Howling at the Moon, 2018), which deals with Acehnese politics during the Military Operations Era. This article borrows its theoretical framework from Fairclough, Bourdieu, and Gramsci, using the concept of power relations to investigate the novels Dasamuka and Lolong Anjing di Bulan. It finds that such power relations are strongly evident in both novels, particularly in their depictions of: (1) language as capital, (2) dominance and hegemony, and (3) opposition to outside dominance. This study finds that, in these novels, power relations have economic roots. Power is exerted, for instance, through (1) the taxation of civilians by the Yogyakarta Palace and the Dutch colonial government; (2) the land rental system implemented by the British and Dutch colonial regimes, which resulted in all profits flowing to these regimes, the Palace becoming economically dependent on these regimes, and the common people being reduced to laborers, and (3) natural gas exploration in Aceh, with all profits flowing to the Indonesian and American governments. Power relations in these novels, thus, are structured by economic factors, reflecting a Marxist paradigm. This reflects the Marxist view that economic factors are foundational for the class structure of society.